PERAN AGURU PENDIDIKAN AGAMA ISLAM DALAM MENGATASI PENGARUH MEDIA SOSIAL DI SMA NEGERI 1 BATU KETULIS - Andi Sugiartu; Bahrul Ulum; Mutiara Citra (Jurnal Manajemen Pendidikan Islam Al-Idarah, 2022)
This study examines the role of Islamic religious education teachers in overcoming the influence of social media at SMA Negeri 1 Batu Ketulis. The problem in this study is what are the roles of PAI teachers in overcoming the influence of social media at SMA Negeri 1 Batu Ketulis and the influence of social media on student achievement at SMA Negeri 1 Batu Ketulis. The purpose of this study was to find out and understand the role of PAI teachers in overcoming the influence of social media at SMA Negeri 1 Batu Ketulis and to find out and understand what influence social media has on student achievement at SMA Negeri 1 Batu Ketulis. This study uses a qualitative approach with descriptive analysis method. In collecting data, the authors used three methods, namely observation, interviews and documentation. The focus of the research was students in grades X, XI and XII at SMA Negeri 1 Batu Ketulis. The results of the study showed that the high use of social media at SMA Negeri 1 Batu Ketulis made the role of Islamic religious education (PAI) teachers in overcoming the influence of using social media at SMA Negeri 1 Batu Ketulis very high, while the use of social media facilitated teaching and learning activities, and had an important role. high on student achievement at SMAN 1 Batu Ketulis.